ANALISA PENGGUNAAN SECONDARY FREQUENCY TERHADAP PELAYANAN LALU LINTAS UDARA PADA UNIT FLIGHT SERVICE STATION (FSS) DI PERUM LPPNPI CABANG AMBON - Rico Yudhi Syaputra Simbolon; Abdul Mu’ti Sazali; Syahrul Aman (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
In providing air traffic services, good communication is needed between Ambon FSS and aircraft and vice versa or what is commonly called Air-Ground communication. Good communication must be established between the FSS unit and the aircraft so that the aircraft itself can receive the information provided by the FSS unit properly which has an impact on the safety and security of the flight itself. Communication disturbances in guiding flight communication at the Ambon FSS Unit in the form of the entry of aircraft pilot voices that are not traffic to Ambon FSS have an impact and disturb flight communication personnel. The purpose of this study was to determine the use of secondary frequency in the FSS unit of Perum LPPNPI Ambon Branch has been carried out properly so that communication between ACO personnel and aircraft can run well so that flight safety and security can be carried out properly. The method used in this research is descriptive qualitative, namely research with qualitative data types, in the form of statements, sentences, and documents. Data collection techniques using the method of observation, interviews, documentation and literature study. The results of the research that the author has done can be concluded that communication interference due to the use of the same frequency interferes with communication between communication personnel and pilots at Perum LPPNPI Ambon Branch. Therefore, it is necessary to have a backup frequency or a secondary frequency on Ambon FSS so that the flight service station service delivery becomes more optimal.